Use of nicotine products and withdrawal support among personnel of the Finnish Defence Forces - Danielsson, Maria; Lammi, Aleksi; Sandström, Per; Siitonen, S; Ruohola, Juha-Petri; Ollgren, Jukka; Pylkkänen, Liisa; Vasankari, Tuula (BMJ, 2026)
Introduction: While the health hazards of smoking are well known, the harmful effects of smokeless tobacco (snus) and other nicotine products remain less familiar. This study investigates the prevalence and habits of tobacco use among Finnish Defence Forces (FDF) personnel, focusing on the use of snus and preferred withdrawal support.
Methods: An electronic questionnaire survey was conducted among FDF personnel in 2014 and 2020. The response rates were 18% in 2014 (n=2386) and 27% in 2020 (n=3373). The study examined demographic factors, smoking, snus and e-cigarette use, and preferences for withdrawal support.
Results: Daily smoking decreased significantly from 14% in 2014 to 6% in 2020, while daily snus use increased from 8% to 11%. E-cigarette use remained low (<1% in 2020). The highest prevalence of snus use was among military personnel working with conscripts. About a quarter of snus users (27%) used snus with a nicotine content of 11-20 mg/g and 30% used snus with a nicotine content of 21-30 mg/g. Preferred withdrawal support included nicotine replacement therapy or medication provided by the employer. A significant number of both smokers and snus users did not receive advice to quit from healthcare professionals.
Conclusions: Tobacco use among FDF personnel shows a decrease in smoking but an increase in snus use. There is a need for targeted cessation support programmes, with an emphasis on professional advice and employer-provided nicotine replacement therapy. Increased involvement of healthcare professionals in advising quitting could significantly enhance cessation rates.